Controlling the Adsorption of Carbon Monoxide on Platinum Clusters by Dopant‐Induced Electronic Structure Modification. Issue 37 (28th July 2016) - Ferrari, Piero; Molina, Luis M.; Kaydashev, Vladimir E.; Alonso, Julio A.; Lievens, Peter; Janssens, Ewald
Abstract: A major drawback of state‐of‐the‐art proton exchange membrane fuel cells is the CO poisoning of platinum catalysts. It is known that CO poisoning is reduced if platinum alloys are used, but the underlying mechanism therefore is still under debate. We study the influence of dopant atoms on the CO adsorption on small platinum clusters using mass spectrometry experiments and density functional calculations. A significant reduction in the reactivity for Nb‐ and Mo‐doped clusters is attributed to electron transfer from those highly coordinated dopants to the Pt atoms and the concomitant lower CO binding energies. On the other hand Sn and Ag dopants have a lower Pt coordination and have a limited effect on the CO adsorption. Analysis of the density of states demonstrates a correlation of dopant‐induced changes in the electronic structure with the enhanced tolerance to CO poisoning. Abstract : Gas‐phase reactions : The influence of dopant atoms on the carbon monoxide adsorption on small platinum clusters was studied by mass spectrometry (see picture) in combination with density functional calculations. The results show a correlation of the dopant coordination and the dopant‐dependent charge transfer with the CO adsorption energy.